Accounting for cross-country differences in intergenerational earnings persistence: The impact of taxation and public education expenditure - Hans A. Holter (Uppsala University, Department of Economics, 2011)
I document a strong negative cross-country correlation between intergenerational earnings persistence and tax progressivity, and between intergenerational earnings persistence and public expenditure on tertiary education. To explain these correlations I then develop an intergenerational life-cycle model of human capital accumulation and earnings, which features, progressive taxation, public education expenditure, and borrowing constraints among the determinants of earnings persistence. I calibrate the model to US data and use it to decompose the contributions to earnings persistence from different model elements and to quantify how earnings persistence in the US changes as I introduce tax- and eduction expenditure policies from other countries. I find that individual investments in human capital accounts for 62% of the estimated intergenerational earnings persistence in the US. Taxation, through its impact on investments in human capital, can explain 25% of the difference between the US and 10 other countries, whereas borrowing constraints have a limited impact on earnings persistence.
urn:nbn:se:uu:diva-165479
Keywords: E24; E62; H31; H52; J62; J68; 330; Intergenerational Earnings Persistence; Taxation; Public Education Expenditure; Lebenseinkommen; Generationengerechtigkeit; Steuerprogression; Bildungsfinanzierung; Dekompositionsverfahren; USA; OECD-Staaten